ASSOCIATION BETWEEN NON-PHARMACOLOGICAL METHODS (KANGAROO-MOTHER CARE METHOD AND BREASTFEEDING) AND LENGTH OF HOSPITAL STAY IN NEWBORNS WITH NEONATAL HYPOGLYCEMIA IN A PUBLIC MATERNITY HOSPITAL IN MANAUS - Rodrigo Otávio Barroso Collares Louzada; Rafael José de Castro Costa; Ana Caroline Cortez de Souza; Pamela de Fátima Cavalcante Lira; Renata Ferreira dos Santos; Elaine Santana Cordovil; Winnie Lagoa de Souza (Artefactum - revista de estudos interdisciplinares, 2026)
Neonatal hypoglycemia is a common condition among newborns, especially preterm and low-birth-weight infants, and can be prevented and managed through strategies such as breastfeeding and the Kangaroo Care Method. The objective of this study was to describe the use of the Kangaroo Care Method and exclusive breastfeeding and their association with the length of hospital stay for newborns with neonatal hypoglycemia in a Kangaroo Neonatal Intermediate Care Unit (UCINCa) at a public maternity hospital in Manaus, Amazonas, from 2022 to 2024. This is an epidemiological, observational, retrospective, and documentary study based on the analysis of 280 medical records, of which 128 comprised the final sample. The data were analyzed using descriptive and inferential statistics, with a significance level of 5% (p < 0.05), applying Pearson’s chi-square, Student’s t, and Mann-Whitney tests, depending on the normality of the data. There was a predominance of moderate preterm newborns (60.9%), with low birth weight (49.2%) and delivered by cesarean section (64.8%). Exclusive breastfeeding was practiced in 63.3% of cases, and the Kangaroo Care method in 58.5% of cases. The overall mean length of hospital stay was 9.6 days, with a median of 7 days. Newborns who were exclusively breastfed had a shorter mean length of hospital stay (7 days) compared to those who were not (8.6 days; p=0.031). Among those who received the Kangaroo Care method, the average length of hospital stay was 7.3 days, compared with 7.8 days among those who did not (p=0.042). It is concluded that exclusive breastfeeding and the Kangaroo Care method were associated with a shorter length of hospital stay among newborns with neonatal hypoglycemia, reinforcing the importance of these non-pharmacological, humanized practices in neonatal care in maternity hospitals in the Amazon region.